Impacts of Multiple Stressors on a Benthic Foraminiferal Community: A Long-Term Experiment Assessing Response to Ocean Acidification, Hypoxia and Warming - Bernhard, Joan M.; Wit, Johannes C.; Starczak, Victoria R.; Beaudoin, David J.; Phalen, William G.; McCorkle, Daniel C. (Frontiers in Marine Science, 2021)
Ocean chemistry is changing as a result of human activities. Atmospheric carbon dioxide (CO2) concentrations are increasing, causing an increase in oceanic pCO2 that drives a decrease in oceanic pH, a process called ocean acidification (OA). Higher CO2 concentrations are also linked to rising global temperatures that can result in more stratified surface waters, reducing the exchange between surface and deep waters; this stronger stratification, along with nutrient pollution, contributes to an expansion of oxygen-depleted zones (so called hypoxia or deoxygenation). Determining the response of marine organisms to environmental changes is important for assessments of future ecosystem functioning. While many studies have assessed the impact of individual or paired stressors, fewer studies have assessed the combined impact of pCO2, O2, and temperature. A long-term experiment (~10 months) with different treatments of these three stressors was conducted to determine their sole or combined impact on the abundance and survival of a benthic foraminiferal community collected from a continental-shelf site. Foraminifera are well suited to such study because of their small size, relatively rapid growth, varied mineralogies and physiologies. Inoculation materials were collected from a ~77-m deep site south of Woods Hole, MA. Very fine sediments (<53 µm) were used as inoculum, to allow the entire community to respond. Thirty-eight morphologically identified taxa grew during the experiment. Multivariate statistical analysis indicates that hypoxia was the major driving factor distinguishing the yields, while warming was secondary. Species responses were not consistent, with different species being most abundant in different treatments. Some taxa grew in all of the triple-stressor samples. Results from the response of this continental shelf benthic foraminiferal community suggest that foraminiferal species’ responses will vary considerably, with some being negatively impacted by predicted environmental changes, while other taxa will tolerate, and perhaps even benefit, from deoxygenation, warming and ocean acidification.